2019
DOI: 10.1590/1808-057x201806320
|View full text |Cite
|
Sign up to set email alerts
|

Market reaction to bank merger and acquisition events in Brazil: an analysis of the effects of market waves

Abstract: The aim of this study is to investigate the stock market’s reaction to bank merger and acquisition (M&A) events in Brazil when the market is heated. This article aims to fill the research gap involving bank M&As and their effects, especially those arising from M&A waves. This field remains open in the literature; there is no consensus as to the abnormal returns the investor can expect from this mechanism. The notion that bank M&A markets heat up is discussed and still does not present a consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(127 reference statements)
1
2
0
Order By: Relevance
“…Similarly, this study has empirically investigated the effect of merger and acquisition on bank performance and found that mergers and acquisitions have a significant positive effect on the bank performance. These results are in agreement with the discourse of several studies that have also explored the effect of merger and acquisition on the bank performance (Abdulazeez et al, 2016;Arena & Dewally, 2017;Christine & Jagongo, 2018;Souza & Gartner, 2019). This also confirms that, the study's position and prior argument raised by Hassen et al (2018) that in the long run merger and acquisition achieve all their aims.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, this study has empirically investigated the effect of merger and acquisition on bank performance and found that mergers and acquisitions have a significant positive effect on the bank performance. These results are in agreement with the discourse of several studies that have also explored the effect of merger and acquisition on the bank performance (Abdulazeez et al, 2016;Arena & Dewally, 2017;Christine & Jagongo, 2018;Souza & Gartner, 2019). This also confirms that, the study's position and prior argument raised by Hassen et al (2018) that in the long run merger and acquisition achieve all their aims.…”
Section: Discussionsupporting
confidence: 91%
“…However it yet remains unclear, because of mixed results from empirical studies (Lebedev et al, 2015). Souza and Gartner (2019) reported that in the most recent times, the global economy, particularly in the banking sector, has realized an increase in the incidence of mergers and acquisitions. Some researchers argued that cross-border investment could lead to the inflows of capital and do not only bring in the needed capital but have positive implications on productivity and investment that can improve the host country's business performance (Miozzo et al, 2016).…”
Section: The Relationship Between Merger and Acquisition And Bank's Performancementioning
confidence: 99%
See 1 more Smart Citation